THE IMPACT OF THE COVID-19 PANDEMIC ON ANGKLUNG STAGE EVENT IN THE BANDUNG REGION - At-Thoriq, Muhammad Naufal; Wardhani, Ida Ayu Laksmi Kusuma; Adjani, Jasmine; Prasetyo, Ivan Pratama Darmawan; Ghassani, Annisa; Subandoro, Ilham; Gerren, Gerren (Universitas Lambung Mangkurat, 2023)
Angklung’s show affected by regulations about health protocols to minimize physical contact in this COVID-19 pandemic. Hence, income of angklung’s show in Bandung has decreased and this made angklung community forced to adapt. This research intended to know about the income and to find alternative solution. This research used form deployment and study literature as the method. This research show that angklung’s show income decrease when this pandemic. Benefit from this research can make angklung’s community adapt.